Sociolinguistics and modes of social class signalling: African perspectives. (10th February 2020) - Banda, Felix
Abstract: The paper evaluates spatial, behavioural, and material signalling of social class in African contexts, focusing on Kenya and Zambia. In particular, it draws on notions of mode of class signalling and intersectionality and a vignette of an interaction between urban‐based Western educated development agents and local participants in rural Kenya to illustrate how social class is implicated in interactions. The paper shows how significant features of class and dimensions of social inequality may be perceived intersectionally so that positionalities in class structures are negotiated in contexts of interaction, thus illustrating how structural conditions of class may be challenged and questioned. The paper concludes that sociolinguistics needs to identify the various ways in which the marginalized challenge social structures of inequality. Otherwise there is a risk that sociolinguistics will work to validate inequalities as permanent and fixed, and victims of unequal treatment as permanently condemned and never able to rise against oppressive social structures that tyrannize them. Abstract : Kutenga zitsanzo m'maiko ya Kenya ndi Zambia, pepalayi yaunika malo, macitidwe, zinthu zakuthupi ndi zipangizo zomwe zisonyeza zamakalasi apamwamba ndi apansi. Makamaka, pepalayi yatengela malingalilo amacitidwe osiyanitsa anthu m'makalasi, pakati pa ophunzitsidwa bwino azacitukuko ocokela m'matauni ndi omwe akutenga nawo mbali kumidzi yaku Kenya, kuti ifotokoze momwe magulu ya makalasi osiyana amakhudzila zocitika. Pepala yawonetsa kuti kusiyana kwa magawano m'makalasi ndi kusalingana kwa cikhalidwe zili muzokambilana za anthu. Ici cionetsa kuti magawano m'makalasi angatsutsidwe komanso kufunsidwa munkhani zokambilana. Pepalayi imaliza ndi kuti, akatswili azilankulo ayenela kudziwa ndi kuunikila njila zosiyanasiyana zomwe makalasi omwe ali ozunzidwa amapeza kuti angonjetsa zisankho. Kupanda kutelo pali ciopsezo kuti akatswili azilankhulo azakhalila a umboni wazabodza kuti anthu ozunzidwa sangathe kulimbana ndi kugonjetsa zinthu zopondeleza ndi omwe amawapondeleza.